2004
DOI: 10.1111/j.1464-410x.2003.04757.x
|View full text |Cite
|
Sign up to set email alerts
|

Male genital injury: diagnostics and treatment

Abstract: This article reviews the current status of information on external male genital injuries, focusing on cause, diagnostic and therapeutic management of this uncommon entity. Because of the high risk of infection and the major importance of preserving fertility, male genital injuries represent a serious urological disorder that demands immediate urological treatment. The diagnostic procedure classically consists of taking a history and inspecting the wound; this provides enough diagnostic information for the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 16 publications
0
13
0
4
Order By: Relevance
“…6 A number of studies have reported on the morbidity of burns to the perineum, as well as the optimal treatment method. 2,[7][8][9] The vasculature of the perineum, the surrounding skin and genitourinary function might be compromised after a genital burn. 7 Wessells and Long noted the potential for vascular damage to the genitalia with thermal insult as a result of superficial to deep spreading of the burn leading to destruction of the vascular supply of the genitalia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A number of studies have reported on the morbidity of burns to the perineum, as well as the optimal treatment method. 2,[7][8][9] The vasculature of the perineum, the surrounding skin and genitourinary function might be compromised after a genital burn. 7 Wessells and Long noted the potential for vascular damage to the genitalia with thermal insult as a result of superficial to deep spreading of the burn leading to destruction of the vascular supply of the genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, these infections might destroy surviving epithelial cells and convert partial-thickness burns into full-thickness defects, complicating the "take" of skin grafting. 9 Van der Horst Outcomes of male and female genital burns © 2012 The Japanese Urological Association et al 8 reviewed male genital burns and reported that treating the injury within the first 6 h reduced the risk of infection by implementing wound disinfection and removal of necrotic tissue. Genital burns often lead to genitourinary complications, extended hospital stays and long-term functional complications, such as decreased potency and long-term sexual and urinary dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the external genitalia, in particular to the scrotum, following dog bites are rare when compared to the total number of dog bites. 22,23 In our study dog bite involving the scrotum was extensive and the testis was unsalvageable and the patient ended up with orchidectomy.…”
Section: Dog Bitementioning
confidence: 67%
“…Generally, severe injuries of the external male genitalia are rare because of the location and mobility of the penis and scrotum [1]. Although injuries to the external genitalia are typically not in and of themselves life threatening, they are commonly associated with other potentially life-threatening injuries (for example, to abdomen, pelvis or groin) [2].…”
Section: Introductionmentioning
confidence: 99%